COMPARATIVE STUDIES OF STANDARD STAINLESS STEEL AND IMPROVISED METALLIC IMPLANTS AND CORROSION INHIBITION POTENTIAL OF GUAIACUM OFFICINALE VIA ELECTROCHEMICAL AND COMPUTATIONAL APPROACHES - Nwokem, Nsidibeabasi Calvin; Agbele, Idowu Elijah; Sani, Uba; Omoniyi, Israel Kehinde; Emmanuel, Gaba Echiobi (FUDMA JOURNAL OF SCIENCES, 2023)
The malleability and fabrication of metal and associated alloys, as well as their vast range of applications, are significantly influenced by their physiochemical characteristics. Gas chromatograph mass spectrometer revealed the presence of eight (8) bioactive components, which are responsible for the inhibitory activities. Having a maximum inhibition efficiency of 85.17 at an inhibitor dose of 0.5g/L, there is a significantly reduction in reaction number in the presence of Guaiacum officinale extract compared to the blank solution. The electrochemical parameters for the improvised metallic biomaterial in 1.0 M HCl solution in the presence and absence of inhibitor concentrations revealed the high polarization region, thus a wide potential range. The addition of the inhibitor affected the anodic and the cathodic partial reactions, which signifies mixed-type mechanism of inhibition. The rate of corrosion mitigation increases in the presence of inhibitors when compared with a blank solution as a result of thin-film formation on metal/solution interface. This work give relevant information on the efficiency of Guaiacum officinale as an inhibitor for improvised metallic biomaterial in 1M HCl. The biocompatibility test showed that mechanical and chemical properties are within the recommended values.